2013
DOI: 10.5144/0256-4947.2013.443
|View full text |Cite
|
Sign up to set email alerts
|

Pathological responses and long-term outcome analysis after neoadjuvant chemotheraphy in breast cancer patients from Kuwait over a period of 15 years

Abstract: BACKGROUND AND OBJECTIVESThe attainment of pathological complete response (pCR) after neoadjuvant chemotherapy has been taken as a surrogate marker for disease-free survival and overall survival. This is however dependent on various other parameters such as stage, grade, and biologic markers.DESIGN AND SETTINGSThis is a retrospective study of 365 patients with histologically confirmed non-metastatic breast cancer patients treated with neoadjuvant chemotherapy at the Kuwait Cancer Control Centre between 1998 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…On the other hand, this study uses a variety of potential factors combined with the radiomics signature to build the prediction model, which also improved the accuracy of this model. In this study, we found that ER and PR expression were independent predictors of patients with pCR, which is similar to other studies (37,38). The diagnostic efficacy of the nomogram was higher than the signature after adding pathological indicators, which further demonstrates the important role of hormone receptors in the prediction of pCR status.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, this study uses a variety of potential factors combined with the radiomics signature to build the prediction model, which also improved the accuracy of this model. In this study, we found that ER and PR expression were independent predictors of patients with pCR, which is similar to other studies (37,38). The diagnostic efficacy of the nomogram was higher than the signature after adding pathological indicators, which further demonstrates the important role of hormone receptors in the prediction of pCR status.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, a total of 25 studies were included in the analysis (Figure S1). Among these included studies, there were 4 RCTs (12, 32-34), 2 single-arm clinical trials (35,36), 18 cohort studies (4,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53), and 1 pooled analysis (8) (Table S1). The pooled analysis (Cortazar et al 2014) included 12 neoadjuvant chemotherapy RCTs and patients across different BC subtypes.We only included the results specific to TNBC in the pooled analysis, which were based on 1,157 patients with early-stage TNBC from 4 clinical trials (GeparTrio, GeparQuattro, PREPARE, and EORTC 10994).…”
Section: Literature Search and Description Of Included Studiesmentioning
confidence: 99%
“…8 Previous research has indicated that patients who attain pathological complete response (pCR) to NAC have significantly longer overall survival (OS) and disease-free survival (DFS), particularly for triple negative and HER2+ breast cancer. [9][10][11] It is therefore important to identify those patients who are most likely to benefit from NAC treatment and to understand the advantages of NAC with respect to long-term outcomes. The purpose of this review is to describe the evaluations of NAC efficacy in breast cancer.…”
Section: Introductionmentioning
confidence: 99%